2018
DOI: 10.1002/ldr.3022
|View full text |Cite
|
Sign up to set email alerts
|

How might sediment connectivity change in space and time?

Abstract: Many authors focus on the concept of sediment connectivity to predict the sedimentary signal delivered at catchment outlets. In this framework, the sedimentary signal is seen as an emergent aggregation of local links and interactions. The challenge is then to open black boxes that remain within a sediment cascade, which requires both accurate geomorphic investigations in the field (reconstruction of sequences of geomorphic evolution and description of sediment routes) and the development of tools dedicated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Previous studies demonstrated that different or even diverging perspectives do not negatively influence the knowledge creation processes when interactions between the actors are repeated, positively perceived and sufficiently adjusted to encourage relationship building (e.g. Dewulf et al, 2007). The approaches and results of our study have been presented to connectivity scientists in EU COST Action ES1306 and closely discussed with the leaders of the action's working groups in order to facilitate effective communication within the working groups and the network.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous studies demonstrated that different or even diverging perspectives do not negatively influence the knowledge creation processes when interactions between the actors are repeated, positively perceived and sufficiently adjusted to encourage relationship building (e.g. Dewulf et al, 2007). The approaches and results of our study have been presented to connectivity scientists in EU COST Action ES1306 and closely discussed with the leaders of the action's working groups in order to facilitate effective communication within the working groups and the network.…”
Section: Resultsmentioning
confidence: 90%
“…Second, constructive conflicts may help to improve group communication, e.g. by unravelling different points of view (De Dreu and Weingart, 2003;Krueger et al, 2016) that affect how interdisciplinary group approaches open questions in connectivity science. Although the colour contours Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, constructive conflicts may help to improve group communication, e.g. by unravelling different points of view (De Dreu and Weingart, 2003;Krueger et al, 2016) that affect how interdisciplinary group approaches open questions in connectivity science. Although the colour contours Öberg (2011).…”
Section: Discussion: Towards Shared Mental Models In Connectivity Resmentioning
confidence: 99%
“…Divergent hillslopes have a decreasing rate of change due to parallel and direct movements of runoff toward the outlet and the effect of the lower part of plot on the outlet runoff volume, while parallel hillslopes have a constant rate of head change due to the constant up and down widths of the plot [49]. However, in convergent hillslopes due to a greater area of upward of plot over time, the rate of increase of runoff peak increases [50,51]. The study of the CHs also shows that the start time of runoff and time to concentration increases with increasing soil RCs (Figure 4).…”
Section: Hydrographsmentioning
confidence: 99%